1963
DOI: 10.1042/bj0870265
|View full text |Cite
|
Sign up to set email alerts
|

Carbohydrates in protein. 5. Procedures for the isolation of glycopeptides from hen's-egg albumin and their oxidation by periodate

Abstract: Vol. 87 DOCOSAHEXAENOIC ACID IN OX RETINA 265 of the cyclohexyl esters of the acids produced showed cyclohexyl propionate, dicyclohexyl malonate and dicyclohexyl succinate to be present, the last two in a 5-2: 1 molar ratio (calculated from the areas under the peaks on the chromatogram). Six structures are therefore possible for the docosahexaenoic acid: the double bonds could be at positions 4,7,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
24
0

Year Published

1964
1964
1984
1984

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 67 publications
(29 citation statements)
references
References 37 publications
5
24
0
Order By: Relevance
“…This suggests that 2 moles of D-mannose and 2 moles of acetamido-hexose/mole remain unoxidized by periodate because of inter-unit linkages. Bragg & Hough (1961) and Fletcher, Marks, Marshall & Neuberger (1963) obtained similar results after periodate oxidation of the carbohydrate in ovalbumin.…”
Section: Molar Proportionmentioning
confidence: 67%
See 1 more Smart Citation
“…This suggests that 2 moles of D-mannose and 2 moles of acetamido-hexose/mole remain unoxidized by periodate because of inter-unit linkages. Bragg & Hough (1961) and Fletcher, Marks, Marshall & Neuberger (1963) obtained similar results after periodate oxidation of the carbohydrate in ovalbumin.…”
Section: Molar Proportionmentioning
confidence: 67%
“…The estimation of acid released during periodate oxidation of glycopeptides is, however, unsatisfactory. Thus a glycopeptide from y-globulin showed a steady release of acid during periodate oxidation (Rothfus & Smith, 1962;Clamp &Putnam, 1964), andFletcher et al (1963) found a similar result with ovalbumin glyco-eptide. The glycopeptide was expected to release 1 equiv.…”
Section: ;mentioning
confidence: 90%
“…The major glyeopeptide of human Tamm-Horsfall glyeoprotein was purified from the glycoprotein isolated from pooled urine, as detailed elsewhere (1). Egg*albumine glyeopeptide was prepared aeeordb~g to FLE~e~E~ et al (10). Pronase (Sigma) was purified by acetone precipitation (19).…”
Section: Methodsmentioning
confidence: 99%
“…In such a glycopeptide, the aspartic acid is linked directly to N-acetylglucosamine in the form of 1-L-,3-aspartamido(2-acetarnido)-1,2-dideoxy-,l-D-glucose. Such a carbohydrate-protein linkage was first identified in ovalbumin (21,22), and it appears now to occur in many animal proteins (23). Its presence in plant glycoproteins was first described in soybean hemagglutinin (24) and more recently in bromelain and other plant glycoproteins (25).…”
Section: Resultsmentioning
confidence: 99%